PENGARUH METODE PEMECAHAN MASALAH MELALUI DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMKN 03 MATARAM - Wali, Muh. Rangga; Prayogi, Saiful; Fuaddunnazmi, Fuaddunnazmi (Lensa : Jurnal Kependidikan Fisika, 2015)
This study aims to determine the effect of problem-solving methods through a demonstration of student physics learning outcomes. Research has been done on X level students in high school. The research method used is experiment. The number of samples is 46 students taken from two classes that have the same initial ability. The data obtained is taken from the post-test value. The research hypothesis was tested by using t test statistic. The result of t-test analysis on the learning process shows the value of t-test = 1.740 is greater than t-table = 1.694 (1.740> 1.694). Therefore, Ho is rejected and Ha is not rejected. We conclude that the use of teaching materials using problem-solving methods through demonstrations has a positive impact on student success.